Analisis Ketertarikan Pendidik Terhadap Buku Pintar Bahasa Arab Sebagai Media Pembelajaran - Fadhil Ra'if; Nada Nur Aini; Darmawan (CV. ITTC INDONESIA, 2024)
Learning a foreign language is not an easy matter, because this language is not the native language that we usually use in everyday life. Therefore, we need to understand that language is actually a habit which of course must be practiced frequently to be able to do it. The purpose of making this article is to find out about market research articles on products that the author has made regarding the Arabic Smart Book which is a new breakthrough as a learning medium. The research method used in this research is a quantitative descriptive research method. The results obtained from the market research that the author has carried out are that most educators are attracted to the product that the author has created.